Water quality physical parameters distribution mapping at upstream of dam spillway - Nurhikmah F.; Zawawi M.H.; Zahari N.M.; Hassan N.H.; Yusairah W.N.; Aziz N.A.; Melan A.; Radzi M.R.M.; Hassani A.; Sidek L.M. (American Institute of Physics Inc., 2023)
Water quality monitoring is indispensable for the development of society and health. Water quality can be determined either by individual parameter of any specific interest or by selected a few important parameters to assess the overall quality. A study was conducted at one of hydropower dam station in Malaysia to identified the pattern of water quality distribution using Surfer software involving turbidity (Tur), total suspended solids (TSS), and total dissolved solids (TDS) on the upstream area of the dam. The parameters were measured at six different points on different depth. The pattern of distribution from upper stream to downstream dam spillway has been determine using colour contour mapping. The results of the analysis showed that the highest value for turbidity is >1000 NTU, for TSS is >1000 mg/l and for TDS is 39 mg/l. 2019 Author(s).